2017
DOI: 10.1007/s40974-017-0074-7
|View full text |Cite
|
Sign up to set email alerts
|

Traditional agriculture: a climate-smart approach for sustainable food production

Abstract: Sustainable food production is one of the major challenges of the twenty-first century in the era of global environmental problems such as climate change, increasing population and natural resource degradation including soil degradation and biodiversity loss. Climate change is among the greatest threats to agricultural systems. Green Revolution though multiplied agricultural production several folds but at the huge environmental cost including climate change. It jeopardized the ecological integrity of agroecos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
146
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 241 publications
(154 citation statements)
references
References 294 publications
(231 reference statements)
2
146
0
6
Order By: Relevance
“…As a result, the biodiversity of the area where IK farming systems has been applied is more abundant and influences an increased quality of vegetation than in NIK-farmed areas. It may be noted that our findings coincided with other such studies on biodiversity and indigenous farming systems [90][91][92]. The variety of species thus will have an anti-erosion effect through the mechanisms that alter rainfall properties [93].…”
Section: Soil Erosion Risk and Indigenous Farming Systemsupporting
confidence: 89%
“…As a result, the biodiversity of the area where IK farming systems has been applied is more abundant and influences an increased quality of vegetation than in NIK-farmed areas. It may be noted that our findings coincided with other such studies on biodiversity and indigenous farming systems [90][91][92]. The variety of species thus will have an anti-erosion effect through the mechanisms that alter rainfall properties [93].…”
Section: Soil Erosion Risk and Indigenous Farming Systemsupporting
confidence: 89%
“…One of the techniques found was integrated crop-animal farming. The integration of animal husbandry with crop cultivation promotes agrobiodiversity, food diversity and resource management that strengthens the resilience of the agroecosystem to climate change [53]. The rice-buffalo co-culture system in Ba'kelalan is an age-old farming practice.…”
Section: Customary Land and Resource Managementmentioning
confidence: 99%
“…The awareness of changing rainfall patterns and extreme temperature impacted the adoption of intercropping negatively (Table 3 (E)) and significantly influenced the adoption of intercrops. These results are inconsistent with other studies, for example, Kassie et al (2012), and Singh & Singh (2017). These studies reported that intercropping as a climate-smart agricultural practice that can help smallholder farmers to reduce risk and improve crop yield productivity.…”
Section: Factors Influencing the Adoption Of Intercroppingmentioning
confidence: 58%